Pediatric Compounding Pharmacy: Taking on the Responsibility of Providing Quality Customized Prescriptions - Tricia Heitman; A. J. Day; August S. Bassani (MDPI AG, 2019)
Compounding pharmacy has an important role to play in the field of pediatric medicine. These specialized pharmacies can offer solutions to the unique patient needs that arise in the pediatric population. Medication can be tailored to the child to allow better compliance in cases when the commercial product is unable to meet the needs of the patient. For example, a suspension, suppository, or lozenge formulation is sometimes needed when the manufactured products are only offered as solid oral dosage forms. Sensory processing disorder (SPD), patients with food allergies, and specific dietary needs can also be a big challenge for caregivers and practitioners who need alternatives to the commercially available forms. Three example cases are presented to help describe the process of collaboration between the pharmacist, patient, and doctor to solve the patient’s needs.